2022
DOI: 10.1126/sciadv.abm0397
|View full text |Cite
|
Sign up to set email alerts
|

Emergent properties of species-habitat networks in an insular forest landscape

Abstract: Deforestation and fragmentation are pervasive drivers of biodiversity loss, but how they scale up to entire landscapes remains poorly understood. Here, we apply species-habitat networks based on species co-occurrences to test the effects of insular fragmentation on multiple taxa—medium-large mammals, small nonvolant mammals, lizards, understory birds, frogs, dung beetles, orchid bees, and trees—across 22 forest islands and three continuous forest sites within a river-damming quasi-experimental landscape in Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 67 publications
(101 reference statements)
0
12
0
1
Order By: Relevance
“…A number of studies have demonstrated that habitat loss and insular fragmentation cause species local extinctions across lowland tropical forests (Gibson et al, 2013; Moore et al, 2022; Palmeirim et al, 2022; Pinto Henriques et al, 2021). Here, we contribute to fill an important knowledge gap by accordingly demonstrating overall negative bats response to disturbance across an insular fragmented landscape in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated that habitat loss and insular fragmentation cause species local extinctions across lowland tropical forests (Gibson et al, 2013; Moore et al, 2022; Palmeirim et al, 2022; Pinto Henriques et al, 2021). Here, we contribute to fill an important knowledge gap by accordingly demonstrating overall negative bats response to disturbance across an insular fragmented landscape in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…By flooding the lowland areas, dam construction often creates insular forest fragments matching the previous hilltops that become isolated within an inhospitable aquatic matrix (Lees et al, 2016). Although recent efforts have been made to understand the ecological consequences of hydropower (Palmeirim et al, 2022; Terborgh et al, 2009), few studies have targeted the Southeast Asian forests (Jones et al, 2016). Such understanding is therefore considered a priority for biodiversity conservation in the region (Coleman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the two continuous old-growth forest sites, we assigned an area value that was one order of magnitude larger than the size of the largest forest patch, measured on a log 10 scale. This approach is commonly employed in studies investigating species-area relationships (SARs; Palmeirim et al 2021Palmeirim et al , 2022. Management history and cattle intrusion were obtained from direct observations of cattle presence within the patches, indirect evidence (dung and tracks), and information provided by local landowners.…”
Section: Methodsmentioning
confidence: 99%
“…By flooding lowland areas, damming creates a myriad of insular forest fragments of various sizes and isolations, sitting on a uniformly inhospitable water matrix. Hydroelectric reservoirs therefore represent unique experimental settings to study the effects of habitat amount and configuration without confounding matrix or strong local-history effects (Diamond 2001; Palmeirim et al 2022; Semper-Pascual et al 2021). Using acoustic detectors, we surveyed bats across 28 landscapes of varying forest cover, edge density and number of patches at the landscape-scale.…”
Section: Introductionmentioning
confidence: 99%